2001
DOI: 10.1165/ajrcmb.25.1.4194
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profile of Bronchoalveolar Lavage–Derived CD4+, CD8+, and γδ T Cells in People with Asthma after Segmental Allergen Challenge

Abstract: T cell-derived cytokines play an important role in the pathogenesis of allergic asthma, but little is known about the cytokine profile of their different subsets. The aim of the present study was to investigate the cytokine production potential of CD4(+), CD8(+), or gammadelta(+) T cells derived from the bronchoalveolar space of mild atopic asthmatic subjects (n = 11) and nonatopic control subjects (n = 9) before and 24 h after segmental allergen challenge. The cytokine production was determined using the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 44 publications
2
56
1
1
Order By: Relevance
“…In addition to determining the percentage of Th2 cells present before and after segmental allergen challenge, we determined the percentage of Th1 cells present in the asthmatic airway because IFN-␥ may play an important role in either increasing or decreasing the severity of the asthmatic response (5,6). After stimulating cells with PMA and ionomycin, we observed that the percentage of IL-4-producing BAL T cells was similar before and after segmental allergen challenge, while the percentage of IFN-␥-producing BAL T cells was somewhat decreased following segmental allergen challenge, similar to a previous study (29,36). We also noted that in the absence of exogenous stimulation with PMA and ionomycin that the percentage of IL-4-producing BAL T cells was unchanged, but that the percentage of IFN-␥-producing cells was decreased significantly as compared with stimulated BAL T cells.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to determining the percentage of Th2 cells present before and after segmental allergen challenge, we determined the percentage of Th1 cells present in the asthmatic airway because IFN-␥ may play an important role in either increasing or decreasing the severity of the asthmatic response (5,6). After stimulating cells with PMA and ionomycin, we observed that the percentage of IL-4-producing BAL T cells was similar before and after segmental allergen challenge, while the percentage of IFN-␥-producing BAL T cells was somewhat decreased following segmental allergen challenge, similar to a previous study (29,36). We also noted that in the absence of exogenous stimulation with PMA and ionomycin that the percentage of IL-4-producing BAL T cells was unchanged, but that the percentage of IFN-␥-producing cells was decreased significantly as compared with stimulated BAL T cells.…”
Section: Discussionsupporting
confidence: 89%
“…Increased proportions of IL-5-and IL-13-producing γδ T cells are present in the bronchoalveolar lavage of patients with asthma (36). Accordingly, TGF-β, which is produced in response to allergen challenge (37), might drive the differentiation of local Vδ2 T cells into IL-9 producers.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular cytokine detection of BALF-derived T cells was performed as previously described (49). Briefly, BALF cells isolated from 11 patients were resuspended in RPMI 1640 supplemented with 10% fetal calf serum (Biochrom AG) (1 × 10 6 cells/ml).…”
Section: Methodsmentioning
confidence: 99%